2016
DOI: 10.1080/21655979.2016.1222995
|View full text |Cite
|
Sign up to set email alerts
|

A simple, rapid method for evaluation of transfection efficiency based on fluorescent dye

Abstract: Enhanced transfection efficiency of transient gene expression (TGE) and electroporation is a useful approach for improvement of recombinant therapeutic proteins in mammalian cells. A novel method is described here in which CHO cells expressing recombinant FVII (rFVII) were labeled with fluorescent dye and analyzed by confocal microscopy. Cells with or without rFVII encoding gene were detectable by flow cytometry. Thus, we were able to distinguish positive cells (with rFVII encoding gene) and quantify their per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Filler DNA is both cost‐attractive and can accelerate the process by enabling the production of broad panels of hit sets from small‐scale high‐throughput plasmid preparations. Several publications [ 25,26,27 ] have demonstrated that the addition of irrelevant DNA as Filler or carrier to the transfection process can improve transfection efficiency, alter transcription rates and ultimately increase the amount of protein obtained. Although several mechanisms of action have been proposed, it is not fully understood which mechanisms lead to these benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Filler DNA is both cost‐attractive and can accelerate the process by enabling the production of broad panels of hit sets from small‐scale high‐throughput plasmid preparations. Several publications [ 25,26,27 ] have demonstrated that the addition of irrelevant DNA as Filler or carrier to the transfection process can improve transfection efficiency, alter transcription rates and ultimately increase the amount of protein obtained. Although several mechanisms of action have been proposed, it is not fully understood which mechanisms lead to these benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, transfection effi ciency is evaluated using biomarkers such as luciferase and GFP (7,8,10,11,17,18). In this study, GFP in pEGFP-N1 and pCDH plasmid vectors were used as strong biomarkers for evaluating fl owcytometry.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit these reporter genes are often used interchangeably in transfection experiments, each transgene and respective assay has a different sensitivity and its own metrics [161]. For instance, fluorescent proteins are good descriptors of the transfection efficiency at the single cells level, which is typically defined as the percentage of cells expressing the transgene-encoded protein [162][163][164]. Conversely, luciferase expression provides relevant information about pDNA expression levels within a cell population but not in single cells, as the chemiluminescence is expressed as arbitrary luminescence units per milligram of proteins in cell lysates [165][166][167][168].…”
Section: Evaluation Of Transfection Effectiveness: a Trade-off Betweementioning
confidence: 99%